Pengaruh Strategi Bisnis dan Good Corporate Governance Terhadap Kinerja Perusahaan: Studi Empiris pada Perusahaan Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Naftali Destira Natalia; Azwir Nasir; Rheny Afriana Hanif (Masyarakat Ekonomi Syariah Bogor, 2024)
Company performance is a decision from all agreed factors, therefore to assess company performance by increasing the company's financial performance. The basis for decision making can be seen by measuring the company's financial performance. Company performance is a measure of how well a company uses its assets and other resource to generate income. The study aims to analyze the effect of business strategy and good corporate governance on company performance. The population in this study are Consumer Goods Industry Companies in 2020-2022. The sample in this study were 62 companies obtained through purposive sampling. The data analysis method used is multiple linear regression. The result of this research show that the Business Strategy, the Board of Commissioners, and the Board of Directors influences company performance.